Effectiveness of telerehabilitation versus physical rehabilitation on postural angles in adolescent girls: a cluster randomized controlled trial - Pallavi S. Wakode; Janhvi V. Dongre (International Journal Of Community Medicine And Public Health, 2026)
Background: Postural deviations such as forward head posture and rounded shoulders are increasingly prevalent among adolescents. Despite growing interest in corrective interventions, limited evidence exists regarding their effect on objectively measured postural angles. This study compares the effectiveness of tele-rehabilitation and physical (in-person) rehabilitation on Postural angles in adolescent girls. Methods: A cluster randomized controlled trial was conducted among school-going adolescent girls aged 12-16 years. A total of 120 participants were recruited and allocated into three groups: telerehabilitation (n=40), physical rehabilitation (n=40), and control (n=40). Due to attrition, 114 participants were included in the final analysis. Interventions were delivered three times per week for eight weeks. Postural angles cervical angle, sagittal head angle, and shoulder angle were assessed using photogrammetry. Statistical analysis was performed using a generalized linear model (GLM) adjusting for baseline values. The intervention in tele rehabilitation group was given on an online video platform and physical rehabilitation was given in person in school. Results: Both telerehabilitation and physical rehabilitation demonstrated significant improvements in all postural angles compared to the control group (p